(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
Based on field soil-ameliorative and laboratory-analytical studies, the main properties and ameliorative state of the soils of the foothill plain of the Mirzachol Steppe have been studied, within the territory of the Djizak steppe. The characteristic of the modern salt accumulation is given in connection with the development of irrigation of the territory, as well as the peculiarities of the manifestation of secondary salinization on irrigated lands.